(Re-) Mapping the System: Toward Dialogue-Driven Transformation in the Teaching and Assessment of Writing - Slomp, David Hendrik; Graves, Roger; Broad, Bob (Alberta Journal of Educational Research, 2015)
Over three days, 180 junior and senior high school English teachers, postsecondary (university and college) writing instructors, workplace (corporate and small business) writing instructors, and government officials who are responsible for portfolios related to workforce training and literacy met to understand from a broad systems-level perspective how writing development was being supported and assessed in Alberta Canada. Conversations were structured using Dynamic Criteria Mapping (Broad, 2003) as a method for understanding the values, expectations, and contextual factors that shape the system. Participants shared values related to clarity of expression, risk-taking, and ability to motivate audience. These values, however, were enacted differently within school and workplace contexts. Writing as a problem-solving activity was identified as a tool for enhancing knowledge transfer within the system. Alberta’s large-scale writing exams, on the other hand, created barriers to transfer and development by undermining shared values within the system. Recommendations related to curriculum redesign, pedagogical change, assessment reform, and professional development are suggested for enhancing students’ longitudinal development as writers. Pendant trois jours, 180 enseignants d’anglais au secondaire (de la 7e à la 12e), professeurs d’écriture au post-secondaire (université et collège), enseignants d’écriture en milieu de travail (sociétés commerciales et petites entreprises) et fonctionnaires responsables de dossiers relatifs à la formation et la littéracie en milieu de travail, se sont rencontrés pour déterminer, selon une perspective élargie au niveau des systèmes, dans quelle mesure le développement de l’écriture est appuyé et évalué en Alberta, au Canada. Les conversations étaient articulées sur le recensement de critères dynamiques de Broad, 2003 (Dynamic Criteria Mapping) comme méthode pour comprendre les valeurs, les attentes et les facteurs contextuels qui façonnent le système. Les participants ont fait part de leurs valeurs liées à la clarté de l’expression, la prise de risques et la capacité de motiver un public. Toutefois, ces valeurs ne se manifestaient pas de la même façon dans un contexte scolaire que dans un milieu de travail. En tant qu’activité de résolution de problèmes, la rédaction a été identifiée comme outil pour améliorer le transfert de connaissances au sein du système. Pourtant, les examens à grande échelle portant sur l’expression écrite en Alberta posaient des obstacles au transfert et au développement en ébranlant les valeurs partagées au sein du système. On présente des recommandations touchant une reformulation du curriculum, des changements pédagogiques, une refonte de l’évaluation et le perfectionnement professionnel, le tout visant une amélioration du développement longitudinal de l’expression écrite chez les étudiants.